The Role of Administrative Services in Supporting the Implementation of Efficient Governance in Elementary Schools - Tanjung, Bahdin Nur; Elfrianto, Elfrianto (Lembaga Riset Mutiara Akbar, 2023)
This research investigated the role of Administrative Services (TU) in supporting the implementation of efficient governance in Elementary Schools (SD). Using a qualitative approach, the study involved in-depth interviews, observations, and document analysis to comprehend the role of TU and the impact of information technology integration in the school environment. Findings indicated that TU staff played a crucial role in administrative, financial, and daily operational management, while information technology integration contributed positively to efficiency. Challenges such as resource limitations became a focal point of discussion. The results of this research provide a foundation for the development of best practices and policies at the elementary school level. Future prospects involve a deeper understanding of information technology implementation and TU professionalism. Further studies can explore broader impacts on educational quality and contribute positively to the elementary education system in Indonesia